Effectiveness Training Employee to Improvement Service Hotel at ‎Pullman Bandung - Faris Fathurohman; Dimas Reksa Baihaqi (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
One form of employee development is to provide training to employees to improve hotel services. This training is very beneficial for employees because not only will their performance develop but they will also be ready when they will lead a company. Providing training to employees is an investment for the company not only for individuals, but for the company as a whole, with this training employees are helped to do the existing work, and improve their ability to carry out their work. It was found that there was a positive and significant influence between employee training and improving the quality of hotel services. This study aims to analyze the effectiveness of employee training programs on improving hotel services at Pullman Bandung, the implications of these findings indicate importance investment sustainable under development source Power humans to achieve service excellence.